The Efficacy of Sodium-Glucose Cotransporter 2 Inhibitors in Reducing Repeated Heart Failure Rehospitalizations Among Elderly Patients With Acute Decompensated Heart Failure: The ROSES-HF Study - Amioka, Michitaka; Kinoshita, Hiroki; Fuji, Yuto; Nitta, Kazuhiro; Yamane, Kenichi; Shokawa, Tomoki; Nakano, Yukiko (The American journal of cardiology, 2025)
Sodium-glucose cotransporter 2 inhibitors (SGLT2i) have shown efficacy in reducing heart failure (HF) hospitalizations and cardiovascular mortality in patients with chronic heart failure, across a range of ejection fractions. However, data on their long-term efficacy in preventing recurrent hospitalization after acute decompensated heart failure (ADHF) in elderly patients are limited. This study aimed to assess the long-term effect of SGLT2i on recurrent HF hospitalization in patients aged ≥75 years following their initial ADHF admission. The ROSES-HF study, a multicenter, prospective observational cohort study, enrolled 415 patients aged ≥75 years hospitalized with ADHF. Patients were divided into those receiving conventional medical therapy (without SGLT2i, n = 206) or SGLT2i therapy (n = 209), initiated at a median of 2.1 days postadmission. The incidence of recurrent HF hospitalization and the composite endpoint of HF hospitalization or cardiovascular death were compared. During a mean follow-up of 22.4 months, HF rehospitalization occurred in 65 patients (31.6%) in the conventional therapy group compared to 43 patients (20.6%) in the SGLT2i group, with a significant difference (log-rank test, p = 0.028). The cumulative annualized HF rehospitalization events were 24.1 per 100 person-years in the conventional therapy group versus 15.7 per 100 person-years in the SGLT2i group (p = 0.007). The composite endpoint of HF rehospitalization or cardiovascular death was observed in 77 patients (37.4%) in the conventional group compared to 49 patients (23.4%) in the SGLT2i group (log-rank test, p = 0.017). In conclusion, initiating SGLT2i in elderly patients post-ADHF reduces recurrent HF rehospitalization, underscoring its therapeutic value in this population.